Congenital syphilis in the 21st century: how to overcome the challenges? - Domingues, Carmen Silvia Bruniera; Pinto, Valdir Monteiro (Brazilian Journal of Sexually Transmitted Diseases, 2019)
In 2009, the Pan American Health Organization (PAHO) and the United Nations Children’s Fund (UNICEF) launched the “Regional Initiative for the Elimination of Mother-to-child Transmission of HIV and Syphilis in Latin America and the Caribbean”, commitments which were renewed and expanded in 2016 with the “Action Plan for the Prevention and Control of HIV and Sexually Transmitted Infections (2016-2021)”(1). [....]